2008
DOI: 10.1063/1.2985859
|View full text |Cite
|
Sign up to set email alerts
|

Self-detecting gate-tunable nanotube paddle resonators

Abstract: We have fabricated suspended metal paddle resonators with carbon nanotubes functioning as self-detecting torsional springs. We observe gate-tunable resonances that either tune to higher or to lower frequencies when increasing the dc voltage on the back gate. We attribute the former modes to flexural vibrations of the paddle resonator, while the latter ones are identified as torsional vibrations. Compared to top-down silicon fabricated paddle resonators, nanotube springs have smaller torsional spring constants … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Subsequently Witkamp et al [20] identified the bending mode vibrations of a carbon nanotube. Nowadays the technique has been employed by many groups, not only restricted to carbon nanotubes [76,78,126,82,83,85], but also applied to suspended graphene sheets [103,104], free-hanging semiconducting nanowires [94,96] and charge-density-wave sheets [105]. Furthermore, several variations to the original mixing scheme have been implemented, including FM [85] and AM modulation [126].…”
Section: Frequency Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently Witkamp et al [20] identified the bending mode vibrations of a carbon nanotube. Nowadays the technique has been employed by many groups, not only restricted to carbon nanotubes [76,78,126,82,83,85], but also applied to suspended graphene sheets [103,104], free-hanging semiconducting nanowires [94,96] and charge-density-wave sheets [105]. Furthermore, several variations to the original mixing scheme have been implemented, including FM [85] and AM modulation [126].…”
Section: Frequency Mixingmentioning
confidence: 99%
“…Refs. [125,126,57]), thermal effects [127,122], and electromagnetic (optical) properties [55,62,128].…”
Section: Mechanics At the Nanoscalementioning
confidence: 99%
“…High Q-values combined with high resonance frequencies are an important prerequisite for applications such as single-atom mass sensing [7,8,9] and fundamental studies of the quantum limit of mechanical motion [10]. Single-wall carbon nanotubes present a potentially defect-free nanomechanical system with extraordinary mechanical properties: in particular the high Young's modulus (E = 1.2 TPa) in combination with a very low mass density (ρ = 1350 kg/m3 ) [8,11,12,13]. While these favorable properties…”
mentioning
confidence: 99%
“…The main advantage of the passive frequency methods is that they do not consume power to maintain the tuned state. On the other hand, the second approach does not rely on permanent structural modification, and therefore offers reversible and active tuning capabilities [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Previous works for active frequency tuning utilized the electrostatic spring effect [ 14 , 15 ], the geometry of the capacitors [ 16 , 17 , 18 , 19 , 20 , 21 ], the thermal stressing effect [ 22 ], and thermal expansion [ 23 ].…”
Section: Introductionmentioning
confidence: 99%